2016
DOI: 10.1093/bja/aev477
|View full text |Cite
|
Sign up to set email alerts
|

Randomised comparison of the effectiveness of the laryngeal mask airway supreme, i-gel and current practice in the initial airway management of out of hospital cardiac arrest: a feasibility study

Abstract: 18528625).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 32 publications
2
47
2
Order By: Relevance
“…[1314] A number of randomized clinical trials and a meta-analysis also reported that OLP between i-gel™ and LMA-S™ is similar. [678915] On the contrary to our findings, Chew et al . and Ragazzi et al .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[1314] A number of randomized clinical trials and a meta-analysis also reported that OLP between i-gel™ and LMA-S™ is similar. [678915] On the contrary to our findings, Chew et al . and Ragazzi et al .…”
Section: Discussioncontrasting
confidence: 99%
“…[5] Although a number of randomized controlled trials and a meta-analysis have compared i-gel™ and LMA-S™ in adult patients and found that both the device provided equivalent oropharyngeal leak pressure (OLP). [6789] After reviewing the literature, we did not found any study till now that has compared air-Q™ with either of these two devices in adult patients. Jagannathan et al .…”
Section: Introductionmentioning
confidence: 99%
“…33-35 However, at least 3 currently ongoing randomized phase 3 trials are assessing advanced airway management during cardiac arrest in the out-of-hospital setting (clinicaltrials.gov identifiers NCT02419573 and NCT02327026 and isrctn.com identifier ISRCTN08256118). While these trials assess the efficacy of advanced airway management in the out-of-hospital setting, the results might not translate to the in-hospital setting given important differences in cardiac arrest etiology, skills of health care professionals, and timing of interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the scale of the 3 trials, important scientific questions remain. PART, AIRWAYS‐2, and CAAM evaluated different airway devices; there has been only 1 direct randomized comparison between different SGA devices (eg, LT, i‐gel, or LMA), and none between SGA and BVM in randomized clinical trials enrolling adult OHCA patients . There is also limited information regarding the influence of airway management technique on chest compression continuity.…”
Section: Unanswered Questionsmentioning
confidence: 99%